The least effective pollinator principle: Specialized morphology despite generalized ecology - Pauw, Anton (2020)
The large body of work on the adaptation of plants to pollinators is still somewhat incomplete because most studies focus on one-to-one interactions. How will adaptation proceed in a multi-pollinator environment? According to Stebbins' Most Effective Pollinator Principle, ‘the characteristics of the flower will be moulded by those pollinators that visit it most frequently and effectively.’ To test this hypothesis, we studied the pollination biology of Pelargonium incrassatum (Geraniaceae) in the Namaqualand Region of Southern Africa. This species has a long floral tube and we expected its most important pollinator to have a long proboscis. Contrary to expectations, the most important pollinator was a short proboscid fly (a new species of Prosoeca), while Prosoeca peringueyi, which had a proboscis that matched the floral tube length, was a rare visitor. Consistent with the high degree of trait mismatching, we did not detect selection on tube length at most sites. The paradox of mismatching traits can be resolved by considering the strength of the trade-off involved. Adaptation to the rare species can apparently occur without incurring the cost of reduced pollination by the abundant species. Generally, species may often evolve specialized morphology if they do not incur the cost of ecological specialization.